2013
DOI: 10.1155/2013/285927
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Temporal Relationships between Eye Gaze and Peripheral Vehicle Behavior for Detecting Driver Distraction

Abstract: A car driver's cognitive distraction is a main factor behind car accidents. One's state of mind is subconsciously exposed as a reaction reflecting it by external stimuli. A visual event that occurs in front of the driver when a peripheral vehicle overtakes the driver's vehicle is regarded as the external stimulus. We focus on temporal relationships between the driver's eye gaze and the peripheral vehicle behavior. The analysis result showed that the temporal relationships depend on the driver's state. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Driving at intersections is just a small part of this variety of driving situations and conditions. Similar correlations between driving performance and visual distraction were reported by other researchers (Hirayama et al, 2013;Yang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Driving at intersections is just a small part of this variety of driving situations and conditions. Similar correlations between driving performance and visual distraction were reported by other researchers (Hirayama et al, 2013;Yang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, visual lane analysis can be used for “higher-order tasks”, which are defined by interacting with other modules in a complex driver assistance system (e.g., understanding the driver’s attentiveness—distraction—to the lane-keeping task [272]). Hirayama et al [273] focused on temporal relationships between the driver’s eye gaze and the peripheral vehicles behaviour. In particular, they concluded that the timing when a driver gazes towards the overtaking event under cognitive distraction is later than that under the neutral state.…”
Section: General Discussion and Challenges Aheadmentioning
confidence: 99%
“…The authors of [184] reported a correlation between driving performance and visual distraction by utilizing gaze duration as a detection feature. The existence of such correlation was also confirmed by the authors of [185].…”
Section: Measurement Approachesmentioning
confidence: 99%